Assessing School-Based Management in the Philippines - World Bank Group (World Bank, Washington, DC, 2016)
The purpose of this policy note is to assess the current status of school-based management in elementary and high schools in the Philippines. The findings reported in the note are based on a comprehensive survey of the public education system that tracked public education expenditure and assessed the quality of education services. The note shows that the key elements of an effective school-based management system are in place. However, schools report that they are not yet implementing many of the key aspects of this system. Moreover, parents and local communities still play a very limited role in decision-making and in holding schools accountable. Given the ever increasing amounts of resources that schools now control and the need to give them more flexibility over how to use those funds, this note argues that the role of representative school governing councils could be expanded and efforts made by DepEd to increase awareness among parents and education stakeholders of the useful role they could play in supporting school-based management.